Inclusion Complex of Zerumbone with Hydroxypropyl-β-Cyclodextrin Induces Apoptosis in Liver Hepatocellular HepG2 Cells via Caspase 8/BID Cleavage Switch and Modulating Bcl2/Bax Ratio. (8th May 2013) - Muhammad Nadzri, Nabilah; Abdul, Ahmad Bustamam; Sukari, Mohd Aspollah; Abdelwahab, Siddig Ibrahim; Eid, Eltayeb E. M.; Mohan, Syam; Kamalidehghan, Behnam; Anasamy, Theebaa; Ng, Kuan Beng; Syam, Suvitha; Arbab, Ismail Adam; Rahman, Heshu Sulaiman; et al.
Abstract : Zerumbone (ZER) isolated from Zingiber zerumbet was previously encapsulated with hydroxypropyl- β -cyclodextrin (HP β CD) to enhance ZER's solubility in water, thus making it highly tolerable in the human body. The anticancer effects of this new ZER-HP β CD inclusion complex via apoptosis cell death were assessed in this study for the first time in liver hepatocellular cells, HepG2. Apoptosis was ascertained by morphological study, nuclear stain, and sub-G1 cell population accumulation with G2/M arrest. Further investigations showed the release of cytochrome c and loss of mitochondrial membrane potential, proving mitochondrial dysfunction upon the ZER-HP β CD treatment as well as modulating proapoptotic and anti-apototic Bcl-2 family members. A significant increase in caspase 3/7, caspase 9, and caspase 8 was detected with the depletion of BID cleaved by caspase 8. Collectively, these results prove that a highly soluble inclusion complex of ZER-HP β CD could be a promising anticancer agent for the treatment of hepatocellular carcinoma in humans.